APLIKASI PEWARNAAN BAHAN ALAM MANGROVE (Rhizophora sp) SEBAGAI PEWARNA ALAMI BENANG (KAIN TENUN IKAT) DENGAN JENIS MORDAN YANG BERBEDA - Nova Yolani Loit; Abdonia W. Finmeta; Eka Citra Gayatri Kerihi; Nardi M. Leo (Adisam Publisher, 2025)
This research was conducted in March-April 2025, located in TWAL Teluk Kupang, Tanah Merah Village, Central Kupang District, Kupang Regency, East Nusa Tenggara. This research aims to determine the results of natural dyeing of yarn with the type of mordant lime, salt and alum mordant. This research uses an experimental method with four treatments and three replications, namely PO: without mordant, P1: mangrove substance with lime, P2: mangrove substance with salt, P3: mangrove substance with mordant. The results of the first treatment of mangrove leaves were extracted without mordant or can be called control and produced a basic brownish red/terracotta color. The second treatment, mangrove leaves were extracted and added with lime mordant and produced a pale brown color. The third treatment, mangrove leaves were extracted and added with salt mordant and produced a brownish orange yarn, and in the fourth treatment, mangrove leaves were extracted and added with alum mordant and produced a cream/pale yellow yarn.